STRATEGIES IN TRANSLATING PRONOUN, NUMBER, AND VOICE IN A WALK TO REMEMBER: KAN KUKENANG SELALU (A case study on grammatical equivalence) - Ninuk Krismanti; Agustina Lestary (Vidya Karya, 2016)
Abstract: A Walk to Remember is one of the best-selling novels written by Nicholas Spark. The novel has been translated into Indonesian language by Kathleen S.W. This paper is intended to investigate one of the equivalences of the translation: grammatical equivalence. The study used descriptive qualitative method to analyze translation in the novel. The investigation is aimed to identify strategies used to translate three grammatical features: (1) pronoun, (2) number, and (3) voice. The writers take 100 data for each feature as samples of the study. To compare voicing systems in each version of the novel, all sentences in chapter 1 are taken as samples. Based on the findings, the writers conclude that there are five strategies used in translating pronoun: (1) omitting pronoun, (2) translating pronoun as it is, (3) changing pronoun into its reference, (4) making pronoun shift, and (5) adding pronoun. Furthermore, there are two strategies used to translate singular noun with articles: (1) translating articles with lexical addition, (2) translating articles by omission, and (3) changing singular nouns in the English version of the novel into plural nouns in its Indonesian version. In terms of voice, the translator tends to keep the original voice form of the English version of the novel in its Indonesian translation. Keywords: equivalence, pronoun, number, voice Abstrak: A Walk to Remember adalah salah satu novel laris karangan Nicholas Spark. Novel ini diterjemahkan ke dalam Bahasa Indonesia oleh Kathleen S.W. Tujuan dari penelitian ini adalah menganalisa salah satu kesetaraan penerjemahan, yakni kesetaraan tata bahasa. Penelitian ini menggunakan metode deskriptif kualitatif untuk menganalisis penerjemahan dalam novel tersebut. Analisis ini bertujuan untuk menemukan strategi yang digunakan oleh Kathleen dalam menerjemahkan tiga fitur tata bahasa: (1) kata ganti, (2) nomina, dan (3) aktif/pasif. Penulis mengambil 100 data per fitur bahasa yang diteliti sebagai sampel dalam penelitian ini. Berdasarkan hasil analisa, peneliti menemukan bahwa terdapat lima strategi yang digunakan oleh penerjemah dalam menerjemahkan kata ganti: (1) menghilangkan kata ganti, (2) menerjemahkan kata ganti sesuai dengan aslinya, (3) mengubah kata ganti ke dalam kata benda yang digantikan, (4) mengubah kata ganti, dan (5) menambah kata ganti. Lebih lanjut, untuk menerjemahkan kata benda tunggal yang memiliki kata sandang, penerjemah menerapkan tiga strategi: (1) menerjemahkan kata sandang dengan penambahan leksikon, (2) menghilangkan kata sandang, dan (3) mengubah kata benda tunggal dalam novel versi Bahasa Inggris menjadi kata benda jamak pada versi terjemahannya. Terkait sistem aktif/pasif, penerjemah cenderung mempertahankan kalimat asli dari bahasa sumber dalam menerjemahkan novel A Walk to Remember ke dalam Bahasa Indonesia.